Diagnostics and management of patients with systemic vasculitides - Kucharz, Eugeniusz Józef (Przewodnik Lekarza/Guide for GPs, 2008)
Systemic vasculitides are a heterogeneous group of disorders of unknown cause. Their common feature is inflammation within the vascular wall. Diagnosis of vasculitides is based on coexistence of several signs and symptoms. Determination of antineutrophil cytoplasmic antibodies is important. Management includes administration of glucocorticoids and cyclophosphamide.